Don't Forget About the Teachers! Parent and Teacher BASC-2 Reports of Children on the DSM-5 Autism Spectrum. Issue 3 (2nd July 2016) - Ellison, Kimberly S.; Bundy, Myra Beth; Wygant, Dustin B.; Gore, Jonathan S.
ABSTRACT: The new DSM-5 dimensional framework of Autism Spectrum Disorders (ASD) features severity ratings of social communication (SC) and restrictive/repetitive behaviors (RRB) and little research has been conducted since its inception. There has been a recent increase in the administration and adoption of broadband behavior-rating scales by clinicians, to ascertain a summary of the client's behavior, including use with children on the autism spectrum. One such widely utilized accepted instrument is the Behavior Assessment System for Children, 2nd ed. (BASC-2), a multidimensional measure to assess internalizing and externalizing behaviors as well as adaptive functioning for individuals 2–25 years of age. The current study examined and compared the Parent Rating Scale (PRS) and Teacher Rating Scale (TRS) of the BASC-2 for children on the DSM-5 autism spectrum in order contribute novel information to the BASC-2 literature. Utilizing a sample of 67 children and adolescents with ASD, the PRS and TRS of the BASC-2 were compared using paired sample t-tests to assess for differences in parent- versus teacher-reported behavior patterns. Mean parent ratings for atypicality, functional communication, and withdrawal, and mean teacher ratings for atypicality and withdrawal, were clinically elevated. Mean parent and teacher ratings for adaptability and social skills, and mean teacher ratings for functional communication were in the at-risk range. Parent ratings of adaptability, functional communication, and social skill were significantly more severe than teacher ratings of these same subscales. Implications of these results for the assessment of children and adolescents with ASD are suggested.